GollumFit: An icecube open-source framework for binned-likelihood neutrino telescope analyses - R. Abbasi; M. Ackermann; J. Adams; S.K. Agarwalla; J.A. Aguilar; M. Ahlers; J.M. Alameddine; N.M. Amin; K. Andeen; C. Argüelles; Y. Ashida; S. Athanasiadou; et al. (Computer Physics Communications, 2026)

gSeaGen code by KM3NeT: An efficient tool to propagate muons simulated with CORSIKA - S. Aiello; A. Albert; A.R. Alhebsi; M. Alshamsi; S. Alves Garre; A. Ambrosone; F. Ameli; M. Andre; L. Aphecetche; M. Ardid; S. Ardid; H. Atmani; et al. (Computer Physics Communications, 2025)

Monovalent selective ion exchange membranes: A review on preparation processes, applications, performance criteria and sustainability aspects - H. Rosentreter; C. Scope; T. Oddoy; A. Lerch; J. Meier-Haack (Desalination, 2025)

Application of Semiochemicals to Assess the Biodiversity of Subcortical Insects following an Ecosystem Disturbance in a Sub-boreal Forest - Kamal J. K. Gandhi; Daniel W. Gilmore; Robert A. Haack; Steven A. Katovich; Steven J. Krauth; William J. Mattson; John C. Zasada; Steven J. Seybold (Journal of Chemical Ecology, 2009)

Evidence for predominant clones in a cyclically parthenogenetic organism provided by combined demographic and genetic analyses - L. Haack; J.‐C. Simon; J.‐P. Gauthier; M. Plantegenest; C.‐A. Dedryver (Molecular Ecology, 2000)
Aphids are particularly interesting models in the study of genetic and demographic components of plant adaptation because of their breeding system which combines parthenogenesis and sexual reproduction (i.e. cyclical parthenogenesis), and the frequent emergence of host‐adapted races reported in this group. In this paper, patterns of host adaptation were assessed on local populations of the aphid Sitobion avenae by following their demographic and genetic structure in a maize field for two consecutive years. The existence of putative generalist (polyphagous) or specialized (host‐adapted) genotypes was also investigated by comparing the genotypic distribution of this aphid on maize and other cultivated host plants, using five microsatellite loci. Although population dynamics revealed strong variation in aphid abundance during the colonization period on maize, two genotypes identified at seven additional microsatellite loci were predominant and exhibited stable frequencies over cropping season and between years. Based on present and earlier studies, these two prevalent genotypes were shown to survive on different host plants other than maize, to colonize large geographical zones and to persist parthenogenetically for several years. All these data strongly suggest that these two genotypes are asexual generalist clones that could have been favoured by agricultural practices encountered in western Europe. Besides these two clones, a continual replacement of rare genotypes was observed on maize in both years. Hypotheses involving selection via aphid–plant interactions and natural enemies were proposed for explaining the disappearance of these genotypes on maize.

New York's Battle with the Asian Long-Horned Beetle - Robert A. Haack; Kenneth R. Law; Victor C. Mastro; H. Sharon Ossenbruggen; Bernard J. Raimo (Journal of Forestry, 1997)